Perencanaan dan Pembuatan Webportal dengan Penerapan âMarket Basket Analysisâ - Rahardjo, Vincentius Hadi; Budhi, Gregorius Satia; Santoso, Leo Willyanto (Jurnal Infra, 2015)
The onlinestore "X" is a business entity engaged in clothes and all sorts of accessories. It is effectiveness if to collect data on purchases and sales manually expected with this online portal website can help carry out the customer data as well as its transactions,Website created with the aim to understand the conditions on how make a better communication between the customer and the online shop "X" through a portal website that is able to accommodate the needs of the onlinestore "X" in promoting goods. This Website provide a place for non users onlinestores who want to sell at this website are intended to increase the variety of products and attract buyers for transaction on this website. This website is created using programming languages PHP and SQL. As well as the use of JavaScript to help, while using the MySQL database connection is thus easy to develop his future.To facilitate the user in search of goods, the application of data mining features with the a priori method in which these methods will analyze the habits of the transaction the buyer and the items alternately visited by users to find the relationship between different goods not only by one vendor that but it could be a few sellers. Transaction data and user traffic data is processed by a priori algorithm to generate frequent itemsets that ultimately results in the form apriori table association rules. The addition of the element of time from the time the transaction is expected to also help provide accurate results against the results of the data mining process.